Optically Rewritable Transparent Liquid Crystal Displays Enabled by Light‐Driven Chiral Fluorescent Molecular Switches. Issue 10 (11th January 2019) - Li, Juntao; Bisoyi, Hari Krishna; Tian, Jiajun; Guo, Jinbao; Li, Quan
Abstract: Functional soft materials exhibiting distinct functionalities in response to a specific stimulus are highly desirable towards the fabrication of advanced devices with superior dynamic performances. Herein, two novel light‐driven chiral fluorescent molecular switches have been designed and synthesized that are able to exhibit unprecedented reversible Z / E photoisomerization behavior along with tunable fluorescence intensity in both isotropic and anisotropic media. Cholesteric liquid crystals fabricated using these new fluorescent molecular switches as chiral dopants exhibit reversible reflection color tuning spanning the visible and infrared region of the spectrum. Transparent display devices have been fabricated using both low chirality and high chirality cholesteric films that operate either exclusively in fluorescent mode or in both fluorescent and reflection mode, respectively. The dual mode display device employing short pitch cholesteric film is able to function on demand under all ambient light conditions including daylight and darkness with fast response and high resolution. Moreover, the proof‐of‐concept for a "remote‐writing board" using cholesteric films containing one of the light‐driven chiral fluorescent molecular switches with ease of fabrication and operation is disclosed herein. Such optically rewritable transparent display devices enabled by light‐driven chiral fluorescent molecular switches pave a new way for developing novel display technology under different lighting conditions. Abstract : Reversible photoresponsive chiral fluorescent molecular switches for optically rewritable transparent cholesteric liquid crystal display devices are developed. Both single‐luminescent‐mode and dual‐reflective‐photoluminescent‐mode displays with desirable resolutions are demonstrated.